But her emails! How journalistic preferences shaped election coverage in 2016. (August 2019) - Searles, Kathleen; Banda, Kevin K
While existing work explains how journalists use news values to select some stories over others, we know little about how stories that meet newsworthiness criteria are prioritized. Once stories are deemed newsworthy, how do journalists calculate their relative utility? Such an ordering of preferences is important as higher ranked stories receive more media attention. To better understand how stories are ordered once they are selected, we propose a model for rational journalistic preferences which describes how journalists rank stories by making cost-benefit analyses. When faced with competing newsworthy stories, such as in an election context, the model can generate expectations regarding news coverage patterns. To illustrate model utility, we draw on a unique case – the US 2016 presidential election – to explain how reporters order newsworthy stories (e.g. scandal and the horse race) by observing changes in the volume. Our content data captures coverage featuring Hillary Clinton or Donald Trump on major broadcast and cable networks over 31 weeks. We find that the rational journalistic preference model explains the imbalance of scandal coverage between the two candidates and the dominance of horse race coverage. In 2016, such preferences may have inadvertently contributed to a balance of news stories that favored Trump.